Localization of the Mandibular Canal in a Turkish Population: a Retrospective Cone-Beam Computed Tomography Study - Fahrettin Kalabalik; Emre Aytuğar (Stilus Optimus, 2019)
Objectives: The aim of this study was to determine the location of the mandibular canal at the mental foramen region that is essential in order to prevent injuries to the inferior alveolar neurovascular bundle during mandibular surgical procedures. Material and Methods: The position of the mandibular canal was analysed using cone-beam computed tomography images from 300 Turkish patients, who were referred to Department of Oral and Maxillofacial Radiology, Faculty of Dentistry, Izmir Katip Celebi University for various complaints. The distances of the mandibular canal to the outer superior (D1), inferior (D2), buccal (D3), and lingual (D4) cortical margins were measured at 2 mm distal to the mental foramen. Results: There were 148 (49.3%) males and 152 (50.7%) females with ages ranging from 15 to 74 years (39.15 [SD 17.8]). D1 was significantly greater than D2 and D3 was significantly greater than D4 on both left and right sides. While the mean D1, D2, and D4 in males were significantly greater than in females on both left and right sides. There was no significant difference between D3 in males and females on both left and right sides. Conclusions: The results showed that the mandibular canal was vertically located nearer to the inferior cortical border and horizontally nearer to the lingual cortical border of the mandible at the mental foramen region. Knowledge of the distances of mandibular canal to the outer cortical margins at this region of the mandible will be helpful for surgical procedures.